La Morue Normande, de la conserverie au musée - Florence Levert (In Situ, 2007)
In Fécamp, the factory of La Morue Normande opened in 1950. Initially created to dry cods brought by hundreds of tons, it will undergo many changes until its closing. Thank to its post-beam structure, an easy adaptation is provided. This diversification seems to be symptomatic of the decline of Fécamp industrial fishing. Nowadays, while a processing industry which left the port area a few years ago and the coastal fishing do not relate to each other anymore, the building of La Morue Normande will be soon the location of the new museum of Fécamp.